Carbon partitioning in sugarcane (Saccharum species) - Wang, Jianping; Nayak, Spurthi; Koch, Karen; Ming, Ray (Frontiers in Plant Science, 2013)
Focus has centered on C-partitioning in stems of sugarcane (Saccharum sp.) due to their high-sucrose accumulation features, relevance to other grasses, and rising economic value. Here we review how sugarcane balances between sucrose storage, respiration, and cell wall biosynthesis. The specific topics involve (1) accumulation of exceptionally high sucrose levels (up to over 500 mM), (2) a potential, turgor-sensitive system for partitioning sucrose between storage inside (cytosol and vacuole) and outside cells, (3) mechanisms to prevent back-flow of extracellular sucrose to xylem or phloem, (4) apparent roles of sucrose-P-synthase in fructose retrieval and sucrose re-synthesis, (5) enhanced importance of invertases, and (6) control of C-flux at key points in cell wall biosynthesis (UDP-glucose dehydrogenase) and respiration (ATP- and pyrophosphate-dependent phosphofructokinases). A combination of emerging technologies is rapidly enhancing our understanding of these points and our capacity to shift C-flux between sucrose, cell wall polymers, or other C-sinks.